LZM008, a proposed tocilizumab biosimilar: Pharmacokinetics, safety, and immunogenicity profiles compared with ACTEMRA® in Chinese healthy male subjects - Cao, Guoying; Wang, Jingjing; He, Jinjie; Hu, Yingying; Yang, Haijing; Que, Linling; Gu, Xianghong; Yu, Jicheng; Wu, Xiaojie; Wu, Jufang; Fang, Wei; He, Qing; et al. (Frontiers in Pharmacology, 2023)
Background: To investigate the pharmacokinetics, safety and immunogenicity of recombinant humanized anti-human IL-6R monoclonal antibody injection LZM008 and evaluate the pharmacokinetic similarity between LZM008 and tocilizumab (Actemra®) in Chinese healthy male subjects. Research design and methods: In this randomized, double-blinded, paralleled, two-center Phase I clinical trial, 96 subjects were randomized 1:1 ratio to receive 4 mg/kg intravenous dose of LZM008 or (Actemra®), and evaluated for 28 days. The pharmacokinetic bioequivalence was assessed by the maximum serum concentration (Cmax), the area under the serum concentration-time curve (AUC) from time 0 to the last detectable drug concentration (AUC0-t) , and AUC0-∞.The statistical analysis was conducted by SAS enterprise guide statistical software. Safety was assessed by physical examinations, vital signs, laboratory tests, and electrocardiograms. Anti-drug antibodies (ADAs) were measured by bridged electrochemiluminescence immunoassay. Results: LZM008 (N=49) and Actemra® (N=47) groups showed similar PK properties. After single intravenous infusion of 4 mg/kg LZM008, the Cmax and AUC0-∞ of LZM008 reached at 87.99 μg/mL and 11526.70 h*μg/mL with Tmax 1.98 h, and the half-life (t1/2) was 83.45 h. The 90% confidence intervals of ratios for Cmax, AUC0-t and AUC0-∞ were within the range of 80.00%-125.00%. After infusion, One (2.0%) subject in LZM008 group and three (6.4%) subjects in Actemra@ group showed positive ADA test results. The incidence of treatment emergent adverse events (TEAEs) was comparable in the LZM008 and Actemra@ groups (98.0% versus 100%), with blood fibrinogen decreased and neutrophil counts decreased being the most common TEAEs. Conclusions: The pharmacokinetic characteristics and immunogenicity exhibited by LZM008 were similar to that of the reference product, Actemra®. The safety profiles of LZM008 was similar in the two group with mild-moderate adverse effects.